(untitled) (Sains Humanika, 2021)
Work-family conflict is the topic gaining popularity among social science researchers. The purpose of this study is to examine the relationship between work-family conflict and turnover intention among operational staff at a hotel in Kuala Lumpur. This study is also aimed to identify the level of both variables. 64 respondents participated in the study. Data was gathered through Work-Family Conflict Scale and Roodt’s Turnover Intentions Questionnaire and was analyzed by using descriptive statistics through mean score, frequency and percentage, and inferential statistics through Pearson Correlation. The findings revealed the level of work-family conflict is moderate while turnover intention is high. Moreover, work-family conflict has a moderate positive correlation with turnover intention. Lastly, recommendations are suggested for the organization and future research. One of the suggestions provided to the organization is to incorporate family-supportive behavior among hotel supervisors, while for future studies, researcher recommend to broaden the scope of the study.